Constitutive models for rubber IV : proceedings of the fourth European Conference on Constitutive Models for Rubber, ECCMR 2005, Stockholm, Sweden, 27-29 June 2005 /: proceedings of the fourth European Conference on Constitutive Models for Rubber, ECCMR 2005, Stockholm, Sweden, 27-29 June 2005. (2017) - Unknown
No abstract available